Comprehensive study of the magnetic phase transitions in Tb3Co combining thermal, magnetic and neutron diffraction measurements. (August 2019) - Herrero, A.; Oleaga, A.; Gubkin, A.F.; Frontzek, M.D.; Salazar, A.; Baranov, N.V.
Abstract: A comprehensive study of the magnetic phase transitions in Tb3 Co has been undertaken combining different techniques. Using single crystal neutron diffraction in the paramagnetic state a weak crystal structure distortion from the room temperature orthorhombic structure of the Fe3 C type described with the Pnma space group toward structure with lower symmetry has been observed with cooling below 100 K. At 81 K there is a second order phase transition to an antiferromagnetic incommensurate phase with the propagation vector k = (0.155, 0, 0). As derived from thermal diffusivity measurements, the critical exponents for this transition are very close to the 3D-Heisenberg universality class, proving that the magnetic interactions are short-range but with a deviation from perfect isotropy due to crystal field effects. At T 2  ≈ 70 K there is another magnetic phase transition to a ferromagnetic state whose character is shown to be weakly first order. The low temperature magnetic state has a non-coplanar ferromagnetic structure with strong ferromagnetic components of Tb magnetic moments along the crystallographic c -axis. The application of an external magnetic field B  = 2 T along the c crystallographic axis suppresses the incommensurate antiferromagnetic phase and gives rise to the ferromagnetic phase. The magnetic entropy peak change as well as the refrigerant capacity indicate that Tb3 Co is a competitive magnetocaloric material in this temperature range. Highlights: Combined high resolution techniques to study magnetic phase transitions. A weak crystal structure distortion from the Pnma space group is found. Second order para-antiferromagnetic transition is close to the 3D-Heisenberg class. Direct evidences of weakly first order antiferro-ferromagnetic transition. Tb3 Co is a potential magnetocaloric material.